Synergistic effect of plasma power and temperature on the cracking of toluene in the N2 based product gas - Faisal Saleem; Asif Hussain Khoja; Rabia Sharif; Abdul Rehman; Salman Raza Naqvi; Umair Yaqub Qazi; Kui Zhang; Adam Harvey (Heliyon, 2023)
In this research, a dielectric barrier discharge (DBD) reactor is used to study the cracking of the toluene into C1–C6 hydrocarbons. The combined effect of parameters such as temperature (20–400 °C) and plasma power (10–40 W) was investigated to evaluate the DBD reactor performance. The main gaseous products from the decomposition of toluene include lower hydrocarbon (C1–C6). The cracking of toluene increases with power at all temperatures (20–400 °C). On the otherhand, it decreases from 92.8 to 73.1% at 10 W, 97.2 to 80.5% at 20, 97.5 to 86.5% at 30 W, and 98.4 to 93.7% at 40 W with raising the temperature from 20 to 400 °C. Nonetheless, as the temperature and plasma input power increase, the methane yield increases. At 40 W, the maximum methane yield was 5.1%. At 10 and 20 W, the selectivity to C2 increases as the temperature rises up to 400 °C. At 30 and 40 W, it began to drop after 300 °C due to the formation of methane and the yield of methane increases significantly beyond this temperature.